On Jaggi-Suzuki-Type Hybrid Contraction Mappings. (20th October 2021) - Noorwali, Maha; Yeşilkaya, Seher Sultan
Abstract : The aim of the paper is to introduce the concept of new hybrid contractions that combine Jaggi hybrid type contractions and Suzuki type contractions with w -orbital admissible. We investigate the existence and uniqueness of such new hybrid contractions in theorems and results. Further, an illustrated example is given. With the results of this study, we generalize several well-known results in the recent fixed point literature.